The Effect of Thymoquinone on Interleukin-8 Levels, %FEV1 and CAT Scores in Chronic Obstructive Pulmonary Disease (Jurnal Respirologi Indonesia, 2020)
Background: Chronic obstructive pulmonary disease (COPD) is a characterized by respiratory symptoms and persistent airway obstruction due to alveoli and/or airway abnormalities caused by continuous exposure to harmful particles or gases. Airway inflammation plays an important role in the pathogenesis of COPD. Nigella sativa, known as habbatusauda, contains thymoquinone, which has an anti-inflammatory effect. Airway inflamation improvement was measured based on decreased plasma IL-8 level, maintain the optimization of %FEV1 value and clinical improvement based on the decreased CAT score. Methods: The pretest and posttest experimental clinical trial was carried out in 40 patients with stable COPD in the pulmonology outpatient clinics of Dr. Moewardi Surakarta and dr. Soehadi Prijonegoro Sragen Hospital from 29 June to 3 August 2019. Subjects were grouped into treatment group (n=20) receiving standard therapy along with thymoquinone oil capsules 500 mg/day and placebo group (n=20) receiving standard therapy only for 30 days. Results: The study revealed statistically insignificant decreases of IL-8 level (P=0.052) and %FEV1 value (P=0.943) in the treatment group, while CAT score showed significant decreases in the treatment group (P=0.0005). Conclusion: Thymoquinone administration reduce inflammation as it can lower IL-8 level and improves the clinical condition of patients with stable COPD based on a decrease in CAT score.